Analisis Penerapan Prinsip Collateral Dalam Pembiayaan Mudharabah Pada Bank Syariah Indonesia Kantor Cabang Stabat - Riana, Riana (Jurnal Ekonomi dan Keuangan Syariah, 2022)
Collaterals should get attention that collateral does not cause bad financing to become good financing. In conventional banks, collateral for loans from borrowers is very decisive in the approval of lending. On the other hand, in Islamic banking the method is very different. Because by providing loans in the form of bailouts for the purchase of these goods/assets/capital goods, the operation of Islamic banks basically does not prioritize guarantees from borrowers. The method used in this research is descriptive qualitative, and data collection techniques in this study using observation, and interviews. This study concludes that guarantees in financing using mudharabah financing contracts according to the agreement of classical scholars are prohibited and cause the contract to be invalid because it is contrary to the principle of trust that underlies this contract. However, according to some contemporary scholars and based on current application in sharia banking, guarantees in mudharabah financing are allowed but are not intended to ensure the return of capital, but rather to ensure that the performance of the mudarib is in accordance with the terms of the contract and to prevent moral hazard from occurring. in the form of irregularities by the fund manager. Therefore, the guarantee can only be disbursed if the fund manager is proven to have committed a violation (ta‟addi), negligence (taqshir), or violated a predetermined agreement (mukhalafatu al-syurut).